J27 The effects of music on group motivation and team cohesion among novice to intermediate collegiate rowers - Orzel, Maksymilian (Graduate Journal of Sports Science, Coaching, Management, & Rehabilitation, 2024)
Within university level sport, the opportunity to form friendships, connect and create a sense of enjoyment is fundamental to the student experience. The use of music has been shown to have a positive motivational influence within individual and group physical activity settings when engaging in anaerobic activities. Furthermore, team cohesion can be positively influenced by group music self-selection. Within rowing, music with a high number of beats per minute (bpm) has shown to positively affect performance on an indoor rowing machine. Research within this area has primarily provided its focus towards exercisers or teams within an elite performance setting. Therefore, the aims of this study were to explore whether the introduction of music, through group self-selection and playback can have a positive effect upon the group motivation and team cohesion on novice to intermediate level university rowers when encountering a team anaerobic activity. Twenty novice and intermediate university-level rowers from the same participating university rowing club completed the Group Environment Questionnaire (GEQ) and subsequently a team relay of 2000 m, rowing 500 m each in groups of four, with no music stimulus. Eleven music tracks were selected based upon favoured bands or genres of those rowers, and that they contained at least 152 bpm. Tracks were subsequently presented to the participants who were asked to rate the effectiveness of the audio in terms of motivation and cohesion using the Brunel Group Music Rating Inventory (BGMRI). These scores determined the order of the tracks played for the repeat of the team relay. Once completed, the GEQ was readministered. All measures were used in conjunction with institutional ethics approval (33249-A-Feb/2024- 50074-1). A repeated measures MANOVA analysis found a positive difference in one of the four subscales of the GEQ, Group Integration – Social (GI-S; P = 0.03) F1,19 = 5.54, P < 0.05, Hp2 = 0.27). Surprisingly, a supplementary t-test demonstrated a negative difference in the average number of strokes per minute (spm) during the relay t19 = 2.85, P = 0.01. Whilst the data does not replicate previously reported findings when introducing music to anaerobic indoor rowing training, the significant improvement in GI-S scores highlight some real-world implications. With an understanding of the importance of social cohesion in a university environment and the crucial impact sport can create, there is potential to develop a more robust intervention as a social tool first, before becoming a performance enhancement mechanism.